Process yield and economic trade-offs for enzymatic hydrolysis of alkaline pretreated corn stover. (April 2017) - Nahar, Nurun; Ripplinger, David; Pryor, Scott W.
Abstract: Response surface methodology was used to investigate the interaction of pH, temperature, and enzyme loadings on corn stover hydrolysis rates following soaking in aqueous ammonia pretreatment. Economic tradeoffs were estimated for cellulase and hemicellulase loadings under different hydrolysis conditions. Enzyme loadings had a more significant effect on rates than did pH or temperature. The effect of hydrolysis pH was independent of temperature and enzyme loadings, and the optimal pH for glucose and xylose yields were 4.5 and 4.3, respectively. Conducting hydrolysis at 50 °C rather than 37 °C enables either a 10% glucose yield increase, or a comparable yield with 40% and 65% reduction in cellulase and hemicellulase loadings, respectively. Although yield models showed that hydrolysis rates increase with higher enzyme loadings, economic models showed that optimal cellulase and hemicellulase loadings were as much as 47% and 23% lower, respectively, than the maximum loadings tested. Optimal enzyme loadings change with fluctuations in enzyme costs and ethanol price, but cellulase loadings were more sensitive to these changes than hemicellulase loadings. Enzyme loadings were also more sensitive to enzyme price at lower processing temperatures. Enzyme loadings can be adjusted to increase return based on enzyme costs, ethanol price, and process temperature. Highlights: Different combinations of enzymes can be used to attain the same hydrolysis rates. Enzyme cost and ethanol price influenced enzyme loadings needed to maximize return. Cellulase loadings were more sensitive than hemicellulase to economic input values. Enzyme loadings should be adjusted to maximize return based on process temperature.